Dielectric and electrical properties of Sm2/3Cu3Ti4O12 and Co − V doped Sm2/3Cu3Ti4O12 fabricated by semi wet route - Kumar A.; Singh L.; Verma H.; Lee Y.; Singh N.B.; Tiwary D.; Mandal K. (My University, 2025)
Perovskite oxide has taken the significant consideration of research scholars due to its large dielectric constant and uses in different field of daily life. Sm2/3Cu3Ti4O12 (SCTO) and Sm2/3Cu3Ti3.95Co0.025V0.025O12 (SCTCVO) ceramic materials were synthesized by using cost effective chemical wet route. XRD pattern analysis confirms successful synthesis of SCTO and SCTCVO ceramic. Oxidation states of each element was verified by XPS analysis. EDS spectroscopy proved the presence of each element in both ceramics. Dielectric constant of SCTO ceramic peaked at 1562, measured at 513 K and 1 kHz, whereas SCTCVO peaked at 966, measured at 473 K and 1 kHz. Both ceramics exhibited Maxwell relaxation behavior. However, their lowest recorded values were 307 at 303 K and 1 kHz for SCTO and 282 at 303 K and 1 kHz for SCTCVO. The maximum tangent loss value for SCTO and SCTCVO ceramics were noted as 174 and 128, respectively, at frequencies of 1 kHz and temperatures of 543 K and 563 K. © 2025 Elsevier B.V.